Evaluación del rendimiento de arveja (Pisum sativum) utilizando fuentes orgánicas a diferentes dosis con fines de recuperación y conservación de suelos en el CEASA, Latacunga, Cotopaxi. - Balseca Pruna, Henry Manuel (2022)
In Ecuador, peas (Pisum sativum) are one of the main crops since they are consumed both sweet and dry. The main purpose of this research study was to evaluate the yield of peas (Pisum sativum) using organic sources at different doses for soil recovery and conservation purposes at ‘CEASA’ in the Salache campus, belonging to the Technical University of Cotopaxi. After the analysis of variance, it was determined that there were significant differences for the different variables under study, such as number of pods per plant, number of grains per pod, the weight of the total pod, and the yield obtained in kg/ha, with poultry manure being the best treatment, with a coefficient of variation of 13.99%, 9.9%, 28 .48 and 14.42% performing Tukey's test at 5%. Thanks to the application of the different types of fertilizers, it was possible to show certain improvements in the yield of the crop. When performing the means of the Tukey test at 5%, the result of the treatments of bovine manure, humus, and chicken manure was determined, 2 ranges of statistical significance were found, treatment 3 (chicken manure) was located in the first range A, being the one that had a greater efficiency. Determining that this fertilizer is even more effective than bovine manure because it contains much more nitrogen compared to other fertilizers of animal origin, the plants have a greater amount of nitrogen available quickly. It is shown that earthworm humus is the fertilizer with the highest content of organic matter, and treatment 4 (Control) was located in the last rank B, which did not present a significant relevance in the data.